Effect of blood flow restriction training on health promotion in middle-aged and elderly women: a systematic review and meta-analysis - Feng, Mengyun; Li, Jian; Zhao, Jinzhen; Pan, Xianqi; Wang, Mengyu; Han, Qi (Frontiers in Physiology, 2024)
Background: Physical activities play an important role in alleviating the aging problem and improving the physical fitness of middle-aged and elderly people. Blood flow restriction (BFR) training, also known as pressure training, has been widely used to improve athletes' performance and rehabilitation, which is a relatively novel exercise method for improving the physical fitness of middle-aged and elderly people. The purpose of this study is to conduct a systematic review and meta-analysis of domestic and foreign randomized controlled trial studies on BFR training for middle-aged and elderly women, further explore the impact of BFR training on health status. Methods: Meta-analysis was performed according to PRISMA standards, and charts were drawn using Review Manager 5.4 and Stata 17 software. In this study, the keywords such as "pressure training", "blood restriction training", "elderly women", "KAATSU", "blood flow restriction training" were used on CNKI, China Science and Technology Journal Database, PubMed, Embase, Web of Science, Cochrane Library, EBSCO, Scopus, and randomized controlled trials were searched in all languages. The search was performed from the establishment of database to January 2, 2024. The results of the combined effect were represented by SMD.Results: Among the 681 literature retrieved, 6 eligible English articles were included in this metaanalysis. The overall effect test of the combined effect was performed on 10 groups of data, and the results were SMD = -0.18 (95%CI: -0.91 to 0.56; P > 0.05), the maximum dynamic force of 1RM SMD = 0.97 (95%CI: 0.35 to 1.58; P < 0.05), leg compression force SMD = -0.10 (95%CI: -0.78 to 0.57; P > 0.05), heart rate SMD = 0.33 (95%CI: -2.50 to 3.17; P > 0.05), systolic blood pressure (SBP) SMD = -1.44 (95%CI: -2.17 to -0.70; P < 0.05), diastolic blood pressure (DBP) SMD = -0.69 (95%CI: -2.54 to 1.15; P > 0.05).Conclusion: BFR training had a significant effect on the increase of the maximum dynamic force of 1RM and decrease of blood pressure in middle-aged and elderly women, but there was no significant difference found in heart rate and leg compression force.